Plant defense against virus diseases; growth hormones in highlights. (3rd June 2019) - Islam, Waqar; Naveed, Hassan; Zaynab, Madiha; Huang, Zhiqun; Chen, Han Y. H.
ABSTRACT: Phytohormones are critical in various aspects of plant biology such as growth regulations and defense strategies against pathogens. Plant–virus interactions retard plant growth through rapid alterations in phytohormones and their signaling pathways. Recent research findings show evidence of how viruses impact upon modulation of various phytohormones affecting plant growth regulations. The opinion is getting stronger that virus-mediated phytohormone disruption and alteration weaken plant defense strategies through enhanced replication and systemic spread of viral particles. These hormones regulate plant–virus interactions in various ways that may involve antagonism and cross talk to modulate small RNA (sRNA) systems. The article aims to highlight the recent research findings elaborating the impact of viruses upon manipulation of phytohormones and virus biology.